Analyzing the Fast-Food Marketing Strategies Impacting Consumer Buying Behavior - Gan Kia Hui; Wei Chien Ng; Xin Yao Chia; Sihao Chen; Cheah Yee Cheng; Xue Lin Chieng; Amish Kumar Agarwal; Adelia Nur’Aeni; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
Kentucky Fried Chicken (KFC) has long been a dominant player in the global fast-food industry, known for its distinct fried chicken offerings. This study explores the effect of KFC’s marketing strategies on consumer buying behavior, using the marketing mix framework (4P: Product, Price, Place, Promotion). Primary data were gathered from a survey of 150 consumers in Malaysia via Google Forms, while secondary data included company reports and industry publications. Regression analysis was employed to determine the relationship between the independent variables (product, price, promotion, and place) and consumer buying behavior. Results indicated that product, price, and promotion significantly impact consumer decisions, with the product being the most influential factor (beta = 0.525). Price and promotion also had positive, albeit smaller, effects, while place was statistically insignificant. The R² value of 0.755 suggests that 75.5% of consumer behavior variation can be explained by these factors. These findings underscore the importance of product differentiation and effective promotional strategies in shaping consumer preferences, while the role of physical locations may be diminishing in the fast-food sector due to the rise of delivery services.